UKURAN ORGAN SISTEM REPRODUKSI ITIK JANTAN YANG DISUPLEMENTASI PROBIOTIK MEP+ BERBAGAI DOSIS SELAMA 30 HARI - Chelsy Rirgiyensi; Yulia Sistina; Farida Nur Rachmawati (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Probiotics MEP+ can increase fowl weight and weft efficiency, therefore it is important to know probiotics MEP+ effect at different dosage toward reproduction aspect. This research aimed to examine duck reproduction organ size suplemented with probiotics MEP+ with different dosage within 30 days. This research used Completely Randomized Design (CRD) with 4 treatments with different dosages within 30 days which was without probiotic’s application or control (K), 0,75 ml/kg wefts (P1) dose, 1,5 ml/kg wefts (P2) dose, a n d 3 ml/kg wefts (P3) dose. Each treatment repeated 8 times. Total 40 ducks raised in floor dry cage system. At 31st day of treatment duck reproduction system organ was measured. Whole results show increase average data (±SD) for weight of both right and left testis, and liver weight with highly probiotics dosage it, however the analysis result statistic not significant (P>0,05) except weight of right left testis with duck weight or gonadosomatic indeks (GSI) were very significant (P<0,01) among all treatment at different dosages was compared control. The results is confirmed that probiotic's MEP+ treatment with different dosages within 30 days gave no effect towards duck reproduction system organ size except to gonadosomatic indeks (GSI) male duck.